(untitled) (Proceedings of the Mongolian Academy of Sciences, 2016)
According by soil investigation of Ulaanbaatar city area in 2012 soil heavy metal contamination generally was low. In some areas revealed anomaly high content of Chromium, Lead and Zink exceeding maximum allowed content. But this points a sporadic distributed not covered big area and 7.5-2.7 % of samples are exceeding standard level. The soil ammonium and sulfate content is high comparing with non-polluted pasture soils. Soil ammonium pollution more closely connected with big open markets and “ger horoolol” area. Primary source of sulfate content is air pollution and coal burning. Soil microbiological pollution, E.Coli and anaerobic bacteria level is high. The “ger horoolol” district area becoming main source of microbiological pollution. Improvement of solid waste management and “ger horoolol” area planning is challenging issue to solve a soil pollution problem of Ulaanbaatar city area.